Bifurcations of Traveling Wave Solutions for the Coupled Higgs Field Equation - Shengqiang Tang; Shu Xia (International Journal of Differential Equations)
By using the bifurcation theory of dynamical systems, we study the coupled Higgs field equation and the existence of new solitary wave solutions, and uncountably infinite many periodic wave solutions are obtained. Under different parametric conditions, various sufficient conditions to guarantee the existence of the above solutions are given. All exact explicit parametric representations of the above waves are determined.